Life on the Ganga : boatmen and the ritual economy of Banaras - Doron, Assa (Delhi, 2013)
This intriguing anthropological study investigates how the boatmen of Banaras have repositioned themselves within the traditional social organization and used their privileged position on the river to contest upper-caste and state domination. The author examines the evolution of the boatmen community, drawing on a variety of sources to illuminate the cultural politics of social and economic inequality in contemporary India. Life on the Ganga: Boatmen and the Ritual Economy of Banaras offers insight into recent debates about the cultural and historical forms of social practice and resistance at the juncture between tradition and the global economy, and will therefore appeal not only to anthropologists, but to anyone working in the field of development studies, globalization, religion, politics and cultural studies.
Keywords: Boatmen community-India-Varanasi (Uttar Pradesh)